Reduced vocal activity of resident birds following clearcutting reflects a decline in a few species at highly impacted sites in boreal forests - Chikkanarayanaswamy, Pavan; Laaksonen, Toni; Lauha, Patrik; Baroni, Daniele; Brommer, Jon E. (Elsevier, 2026)
Intensive forestry management, particularly clearcutting, threatens boreal biodiversity by reducing critical habitat for specialist species such as resident forest birds. Research on clearcutting often emphasizes the breeding season, primarily reflecting migratory birds, while year-round resident birds—more exposed to local disturbances—remain understudied. Moreover, cross-sectional studies dominate, limiting our ability to detect the clearcutting’s true impact. Using a Before-After Control-Impact (BACI) design coupled with Passive Acoustic Monitoring (PAM), we investigated how clearcutting affects 12 resident forest birds in Southwest Finland. Acoustic data were collected before (2020) and after (2024) clearcutting across 60 sites: 30 control (uncut) and 30 impact (clearcut) sites. Impact sites were further categorized into low-impact (6.45–<33.87%) and high-impact (>33.87–100%) areas based on the proportion of forest removed within a 100-meter radius. Total vocal activity declined significantly at high-impact sites, whereas species richness showed no clear response. Species-specific analyses revealed negative responses for Crested Tit, Eurasian Treecreeper, and Goldcrest, with Eurasian Treecreeper particularly sensitive, declining at even low-impact sites. In contrast, the Black Woodpecker vocal activity increased at high-impact sites. Our results demonstrate that observed changes stemmed from clearcutting rather than natural variation. Our findings highlight that intensive clearcutting substantially reduces resident bird activity in boreal forests, emphasizing the need for sustainable forest management practices, including tree retention strategies, selective harvesting, and species-specific conservation measures. The present study represents one of the first applications of BACI design with PAM for assessing the clearcutting impacts on resident forest birds, providing valuable insights for evidence-based forest management and biodiversity conservation.